2022
DOI: 10.3390/nu14153038
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Modified Healthy Eating Index (HEI-Flex) to Compare the Diet Quality of Flexitarians, Vegans and Omnivores in Germany

Abstract: Interest in plant-based nutrition has steadily increased in the western world in the recent years. The number of people following a meat-reduced, flexitarian diet is growing continuously. However, little is known about the diet quality of flexitarians compared to vegans or omnivores. Therefore, in this cross-sectional study, the food intake of 94 participants aged between 25–45 years was recorded via a validated food frequency questionnaire and 28 self-designed questions about the consumption of plant-based al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Similar to our results, Clarys et al 4 reported higher scores for vegans compared to omnivores (65.4 ± 8.3 vs 54.2 ± 9.0, respectively) when using the older HEI -2010. Bruns et al 47 found that vegans scored significantly higher when compared to omnivores (61 ± 10 vs 47 ± 9; p < 0.001) in their study when assessed by another adapted version of HEI -2015 47 . Our results have shown to be in line with other studies in the literature, that a reduction in animal-derived foods appears to be accompanied by increased overall diet quality.…”
Section: Discussionmentioning
confidence: 73%
“…Similar to our results, Clarys et al 4 reported higher scores for vegans compared to omnivores (65.4 ± 8.3 vs 54.2 ± 9.0, respectively) when using the older HEI -2010. Bruns et al 47 found that vegans scored significantly higher when compared to omnivores (61 ± 10 vs 47 ± 9; p < 0.001) in their study when assessed by another adapted version of HEI -2015 47 . Our results have shown to be in line with other studies in the literature, that a reduction in animal-derived foods appears to be accompanied by increased overall diet quality.…”
Section: Discussionmentioning
confidence: 73%
“…Of the 137 included articles, 31 articles described the original development of 35 plant-based diet quality indices ( Table 1 [ [13] , [14] , [15] , 18 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ] and Table 2 [ 15 , 18 , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , 55 ]), and the remaining 106 articles applied the 35 plant-based diet quality indices in an independent sample to the original development population ( Supplemental Table 2 ). The 137 included articles were published from 2007 to 2022, with most published in 2022 ( n = 39), 2021 ( n = 41), 2020 ( n = 20), and 2019 ( n = 11).…”
Section: Resultsmentioning
confidence: 99%
“… 0–6 N HEI-flexible (HEI-flex) Bruns et al. 2022 Germany [ 56 ] 1 ) HEI-2015 (39) 2 ) Food intake data from the FFQ 3 ) Questions regarding plant-based alternatives 4 ) Recommendations of the German Nutrition Society guidelines 5 ) WHO guidelines 6 ) Dietary guidelines for Americans FFQ, plant-based alternative products questionnaire, 3-d diet diary 14 Beverages, vegetables, fruit, protein sources, carbohydrate sources, whole meal, nuts and seeds, processed meat and plant-based meat alternatives, milk and dairy products and plant-based dairy alternatives, alcohol, high-energy density foods (sweet), high-energy density foods (fat), drinks with high-energy density, and fats and oils and plant-based fat substitutes Mean daily intake was calculated for each food group by a formula. Ratio between intake and intake recommendation calculated for each food group to create a unique HEI-flex score on the basis of adequacy and moderation principles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations